HIV infection and cerebral small vessel disease are independently associated with brain atrophy and cognitive impairment. (1st June 2019) - Sanford, Ryan; Strain, Jeremy; Dadar, Mahsa; Maranzano, Josefina; Bonnet, Alexandre; Mayo, Nancy E.; Scott, Susan C.; Fellows, Lesley K.; Ances, Beau M.; Collins, D. Louis
Abstract : Objective: The objective of this study is to investigate whether cerebral small vessel disease (CSVD) is more common in virologically suppressed HIV-positive participants compared with HIV-negative controls and examine the potential synergistic effects of HIV and CSVD on brain structure and cognition. Design: Cross-sectional analysis of 119 treated, virologically suppressed HIV-positive and 55 HIV-negative participants. Forty-six HIV-positive and 30 HIV-negative participants had follow-up 2 years later. All participants underwent MRI and neuropsychological testing. Methods: Volume of white matter hyperintensities (WMH) was used as a surrogate measure of CSVD severity. Tensor-based morphometry and cortical modeling estimated brain volumes and cortical thickness, respectively. Rasch measurement theory was applied to neuropsychological test scores to estimate overall cognition. Linear models compared WMH loads, brain volumes, and cognition between groups; evaluated the association of WMH loads with brain volumes and cognition; and tested the interaction between HIV and WMH loads on brain volumes and cognition. Mixed-effects models compared the change in WMH loads between groups. Results: WMH loads and change in WMH loads were similar between the groups. HIV-positive participants had poorer cognition, thinner cortex and reduced subcortical volumes compared with HIV-negative controls. Higher WMH loads were associated with reduced cortical thickness and subcortical volumes and worse cognition, regardless of HIV serostatus. No significant interactions were observed between HIV and WMH loads with regards to brain volumes or cognition. Conclusion: These findings suggest that the contributions of HIV and CSVD on brain atrophy and cognitive impairment are independent but additive processes. This argues that optimizing vascular health may mitigate brain injury and cognitive decline, especially in treated, virologically suppressed HIV-positive individuals.